Structural Engineering of Anode Materials for Low-Temperature Lithium-Ion Batteries: Mechanisms, Strategies, and Prospects - Wang, Guan; Wang, Guixin; Fei, Linfeng; Zhao, Lina; Zhang, Haitao (Nano-Micro Letters, 2024)
The severe degradation of electrochemical performance for lithium-ion batteries (LIBs) at low temperatures poses a significant challenge to their practical applications. Consequently, extensive efforts have been contributed to explore novel anode materials with high electronic conductivity and rapid Li+ diffusion kinetics for achieving favorable low-temperature performance of LIBs. Herein, we try to review the recent reports on the synthesis and characterizations of low-temperature anode materials. First, we summarize the underlying mechanisms responsible for the performance degradation of anode materials at subzero temperatures. Second, detailed discussions concerning the key pathways (boosting electronic conductivity, enhancing Li+ diffusion kinetics, and inhibiting lithium dendrite) for improving the low-temperature performance of anode materials are presented. Third, several commonly used low-temperature anode materials are briefly introduced. Fourth, recent progress in the engineering of these low-temperature anode materials is summarized in terms of structural design, morphology control, surface & interface modifications, and multiphase materials. Finally, the challenges that remain to be solved in the field of low-temperature anode materials are discussed. This review was organized to offer valuable insights and guidance for next-generation LIBs with excellent low-temperature electrochemical performance. Highlights: 1 The working principles and limitations of current anode materials at low temperatures are elucidated. 2 Advantages and emphases of various modification strategies, including structural design, morphology control, surface & interface modifications, and multiphase materials of low-temperature anode materials, are reviewed. 3 Perspectives and challenges in developing novel low-temperature anode materials are discussed.